The Effect of Network Capability and Organizational Learning Capability on Transformational Leadership in Forming Innovative Work Behavior Mediated by Critical Thinking Skills at PT Bank Bukopin, Tbk. - Nina Taniya; Anton Wachidin Widjaja (President University, 2022)
This study aims to examine the effect of network capability and organizational learning capability on transformational leadership in forming innovative work behavior mediated by critical thinking skills. This study used Structural Equation Modeling (SEM) analysis with the AMOS program which involved 115 Branch Managers Regional I-V at PT Bank Bukopin, Tbk. The results of the study prove that Network Capability, Organizational Learning Capability can positively influence Transformational Leadership and mediation of Critical Thinking Skills can positively influence Transformational Leadership to form Innovative Work Behavior. Further research is expected to be able to expand research to other institutions outside banking service institutions, such as the insurance service industry or other sectors that have a wide area coverage.